A study on workability of silica fume and iron dust added concrete. Issue 1 (August 2021) - Jain, Bhupesh; Jain, Vaibhav; Sancheti, Gaurav
Abstract: Workability of concrete is one of the important parameters which decide flowability and ease of placing the concrete. This is influenced by various factors such as shape and gradation of aggregate, water to binder ratio, admixture dosage, supplementary cementitious material, mixing time, rate of mixing, etc. Generally, slump cone test is used to decide the workability of concrete. In this paper, the effect on the workability of concrete after replacing cement with silica fume and sand with iron dust is discussed. Silica fume is replacing cement in the range of 2.5%-15% and iron dust with sand in the range of 5%-30% respectively. Also, the combined effect of silica fume and iron dust on the workability of concrete is discussed.